The rapid infilling of a tide-dominated channel on the southern Yangtze Delta plain during the Medieval Climate Anomaly - Zhuoxuan Wu; Jianwen Wang; Xiaomei Nian; Fengyue Qiu; Zhanghua Wang; Zhanghua Wang (Frontiers in Marine Science)
The response of ports and navigation channels in tide-dominated or tide-influenced estuaries to climate warming is of significant practical relevance. However, studies utilizing sedimentary records to understand these dynamics remain limited. This study investigates the rapid siltation of the palaeo-Qinglong channel during the Song dynasty and its relationship to climate change. Three cores were drilled in the lower reaches of the palaeo-Wusong River, and surface sediment samples were collected from the Huangpu River in the southern plain of the Yangtze Delta. Using AMS 14C and optically stimulated luminescence (OSL) dating, sedimentological and alkaline earth metal analyses, this study explores the formation and silting history of the palaeo-Qinglong channel. The results indicate that the palaeo-channel was formed about 2,000 years ago as a fluvial-dominated channel but transitioned into a tide-dominated environment, as evidenced by the prevalence of muddy sediments. Rapid siltation occurred during the 11th and 12th centuries, characterized by increased Sr content and Sr/Ba ratio, which indicate intensified salinity intrusion. This rapid infilling is attributed to the increased storm frequency during the Song dynasty, which enhanced the mud import into the channel. A brief period of strengthened fluvial processes, characterized by the occurrence of sandy bedload in the sediments near Qinglong Town, likely reflects channel regulation projects undertaken along the lower reaches of the palaeo-Wusong River during the Northern Song dynasty. The findings suggest that the climate warming and relative sea-level rise during the Medieval Climate Anomaly (MCA) amplified tidal processes in the lower palaeo-Wusong River. This study provides valuable insights into fluvial-marine interactions and their implications for managing ports and navigation channels in tidally influenced estuaries.